Analisis Laporan Keuangan Sebagai Alat untuk Menilai Kinerja Keuangan Perusahaan pada PT Multi Bintang Indonesia Tbk - Yulida Army Nurcahya; Rizky Puspita Dewi (P4M STIE Putra Bangsa, 2020)
This study aims to analyze the financial performance of PT. Multi Bintang Indonesia Tbk in 2016, 2017 and 2018. The analytical tools used in this study are liquidity ratios (current ratios and fast ratios), solvency ratios (ratio of total debt to assets and total debt to equity) ratios), and profitability ratios (return on investment and return on equity). The results of the current ratio and quick ratio research in 2017 show that the company's financial condition is quite good, because the debt is less than the assets and profits obtained. Whereas in 2016 and 2018, the company's financial condition was not good because of higher debt. The quick ratio in 2016 shows that the company's financial condition is not good. Based on the measurement of the solvency ratio, an increase in the total debt to asset ratio and the total debt equity ratio in 2016 and 2018 indicate that the financial condition is not in good condition. Judging from the profitability ratio, the decrease in return on assets and return on equity in 2016 and 2018 shows that the company's financial performance is not good because the ratios are not maximized in generating profits.